1969
DOI: 10.1002/ijc.2910040311
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomes in burkitt lymphomas. I. Serial studies in a case with bilateral tumors showing different chromosomal stemlines

Abstract: The chromosornes of a Burkitt lymphoma case were j X o w e r l through a pwiod of three months, including stages before treatment and during trcatment and progression. The patient had bilateral facial tuniors with nietastascs to lymph nodes on either side of the neck. The chromosomal stemlines wore diffiwnt on the left and the right side. Both were diploid, the left side representing the normal karyotype, the right side exhibiting a number of marker chromosomes. This difliwnce characterized both the facial tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1971
1971
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Giemsa staining. Photomicrograph x 1,870. from 31 1M lines nor in 450 cells from 18 lines derived from cord blood lymphocytes experimentally transformed by the virus in virro, even though such lines all appear to show the same general features of transformation as lines from Burkitt tumours (Henle, 1968; Achong, 1 9 7 3~) . Nevertheless, by its very absence in these other lines and the regularity of its incidence in Burkitt lymphoma lines (Manolov and Manolova, 1972) (Table I), the abnormality must be of significance in the tumour-derived material.…”
Section: Discussionmentioning
confidence: 94%
“…Giemsa staining. Photomicrograph x 1,870. from 31 1M lines nor in 450 cells from 18 lines derived from cord blood lymphocytes experimentally transformed by the virus in virro, even though such lines all appear to show the same general features of transformation as lines from Burkitt tumours (Henle, 1968; Achong, 1 9 7 3~) . Nevertheless, by its very absence in these other lines and the regularity of its incidence in Burkitt lymphoma lines (Manolov and Manolova, 1972) (Table I), the abnormality must be of significance in the tumour-derived material.…”
Section: Discussionmentioning
confidence: 94%
“…Although episomal EBV DNA was found in latently infected cells, it was demonstrated that integration of the virus into the host-cell genome has been consistently observed only after in vitro superinfection of EBV-negative Burkitt-lymphoma cell lines (Hurley et al, 1991a). The integration of EBV is important as a mechanism for persistence as well as for virus interaction with cellular genes, particularly those genes involved in cell-growth regulation and tumorigenesis (Gripenberg et al, 1969).…”
mentioning
confidence: 99%
“…Rowley (1 977) reported duplication of lq25-lq32 in 30 patients with various hematological disorders including acute non-lymphocytic leukemia, polycythemia Vera and myelofibrosis, while Gahrton et al (1978) found duplication of the region lq23-lq25 in a range of myeloproliferative disorders. Structural variation in chromosome 1 has also been reported for ovarian carcinomas (Atkin and Pickthall, 1977), breast carcinomas (Jones-Cruciger et al, 1976), colonic cancers (Kovacs, 1978), malignant melanomas (Kakati et al, 1977) and in banded and non-banded cells from lines and biopsies of endemic and nonendemic Burkitt lymphoma (Chu et al, 1966;Gripenberg et al, 1969;Manolov et al, 1971;Hubner and Littlefield, 1975).…”
Section: Casementioning
confidence: 89%